The Addition of Pore Holes in Paving Blocks in an Effort to Increase Infiltration - Oktovia, Eli; Andayono, Totoh (CIVED, 2024)
The problem of waterlogging and surface runoff on impermeable pavement surfaces requires finding new ways to manage water flow, especially from rainwater. The type of permeable pavement that is often used is paving block. The use of paving blocks for pavement materials is expected to reduce puddles that occur after rain. One way is to modify the paving block to be greater in seeping water into the soil. This study aims to determine the extent to which the effect of adding pore holes in paving block can increase water infiltration in surrounding soil. This research was conducted through testing in the Laboratory. The type of research is quantitative with experimental method using a rain simulator tool with variations of paving block. From the research results obtained that the addition of pores in the paving block affects the infiltration that occurs. This is evidenced by the increae in the value of infiltration, the infiltration rate value of normal paving block is 182.92-10.43 mm/hour, 2% ratio is 183.75-10.75 mm/hour, 5% ratio is 190.00-11.30 mm/hour, 7% ratio is 231.33-11.46 mm/hour, 10% ratio is 236.88-17.61 mm/hour. From the test results between pore holes with infiltration rate has a significant relationship of 0.037 (<0,05).